Pengaruh FOMO terhadap Problematic Social Media Use pada Dewasa Awal Pengguna TikTok di Kota Bandung - Fani Apriliani Darusman; Indri Utami Sumaryanti (Bandung Conference Series: Psychology Science, 2022)
Abstract. Along with the development of the digital age, there are various application platforms that provide various interesting features on smartphones, one of which is the TikTok application which currently has the highest download rating. In the use of social media in early adulthood, they already have good self-control. Researchers conducted a survey where the use of TikTok social media at this age used 1-3 hours, sometimes even uncontrolled in 1 access. This can lead to new social anxiety, namely Fear of Missing Out, this behavior can also lead to other negative consequences known as Social Media Use Problems. The purpose of this study was to determine how much influence Fear of Missing Out Probelematic Social Media Use had on adult TikTok users in Bandung. Measurements were made using the Fear of Missing Out Scale (FOMOs) and the Bergen Social Media Addiction Scale (BSMAS). The sample in this study found 280 early adults using TikTok in the city of Bandung. The analysis used is the Simple Regression Test technique. Obtained a significance value of 0.000 <0.05, it can be said that there is a significant effect between Fear of Missing Out on Problematic Social Media Use on TikTok adults in Bandung. The results obtained show an R^2 value of 0.553 which means that 55.3% of Social Media Use Problems are influenced by the Fear of Missing Out variable. Abstrak. Seiring merajanya era digital terdapat kemunculan berbagai platform aplikasi yang menyediakan berbagai fitur menarik dalam smartphone, salah satunya terdapat aplikasi TikTok yang saat ini memiliki peringkat pengunduhan tertinggi. Dalam penggunaan sosmed pada usiadewasa awal sudah memiliki self control yang baik. Peneliti melakukan survei dimana penggunaan sosial media TikTok pada usia ini menggunakan 1-3 jam , bahkan terkadang tidak terkontrol dalam 1 kali pengaksesan. Hal tersebut dapat menimbulkan perilaku kecemasan sosial baru yaitu Fear of Missing Out, perilaku ini juga dapat menimbulkan konsekuensi negatif lain yang dikenal dengan Problematic Social Media Use. Tujuan penelitian ini untuk mengetahui seberapa besar pengaruh Fear of Missing Out terhadap Probelematic Social Media Use pada dewasa awal pengguna TikTok di Kota Bandung. Pengukuran dilakukan dengan menggunakan Fear of Missing Out Scale (FOMOs) dan Bergen Social Media Addiction Scale (BSMAS). Sampel dalam penelitian ini berjumlah 280 orang dewasa awal pengguna TikTok di Kota Bandung. Analisis yang digunakan yaitu teknik Uji Regresi Sederhana. Didapatkan nilai signifikansi 0,000 < 0,05 maka dapat disimpulkan bahwa terdapat pengaruh yang signifikan antara Fear of Missing Out terhadap Problematic Social Media Use pada dewasa awal pengguna TikTok di Kota Bandung. Hasil yang diperoleh menunjukan nilai R^2 sebesar 0,553 yang memiliki arti bahwa 55,3% Problematic Social Media Use dipengaruhi oleh variabel Fear of Missing Out.